Reconceptualization of Public Sector Accountability through Value for Money-Based Performance Audit: A Systematic Literature Review on the Effectiveness of Governance - Reni Susilo Wati; Eskasari Putri (Universitas KH. Abdul Chalim Mojokerto, 2026)
Public sector accountability has become an important issue in governance, especially with the high cases of budget misappropriation indicating a weak public sector audit oversight system. This study aims to reconceptualize public sector accountability through value for money audits in order to improve governance effectiveness. The research method used is a systematic literature review (SLR) covering the period 2016-2026 from 512 articles after the screening stage, 27 articles were analyzed discussing accountability principles, performance audits, recommendation quality, public value, and sustainability. The study results indicate that public sector accountability needs to shift from administrative compliance towards result based, evidence based, benefit based, and public value based responsibility. Value for money based performance audits significantly influence strengthening the evaluation of the economy, efficiency, and effectiveness of public fund usage through inputs, processes, outputs, and outcomes. Audit reports must be supported by valid evidence and produce concrete, measurable, and actionable recommendations. Performance audits are also capable of responding to corruption risks, improving digital governance, emergency management governance, and achieving the SDGs. The implication is that audits are not only tasked with supervision but are also able to increase public trust, evaluate service quality, and promote fair and sustainable development.